Kilka uwag dotyczących stosunku Stanów Zjednoczonych Ameryki do traktatowej ochrony praw człowieka w prawie międzynarodowym - Oręziak, Bartłomiej ("Młody Jurysta" Czasopismo Studentów i Doktorantów Wydziału Prawa i Administracji UKSW, 2017)
This article regards the application of human rights treaties by the USA, their hierarchical relation to the constitution of the United States of America and federal acts. Administration practices have been brought up in reference to international treaties and the manner of their ratification. The main concern is to determine if the lack of ratification of most human rights treaties by the United States of America and the high amount of stipulations reported is affecting the non-observance or worsening standards of concerned issues regulated by these acts, in relation to worldwide guidelines or the legislations of other countries. The article includes an up-to-date list of human rights treaties which have been ratified by the United States of America and the information if USA has reported any reservations.